Paracrine Interleukin 6 Induces Cerebral Remodeling at Early Stages After Unilateral Common Carotid Artery Occlusion in Mice - Melanie T. C. Kuffner; Stefan P. Koch; Stefan P. Koch; Stefan P. Koch; Marieluise Kirchner; Susanne Mueller; Susanne Mueller; Susanne Mueller; Janet Lips; Jeehye An; Jeehye An; Jeehye An; et al. (Frontiers in Cardiovascular Medicine, 2022)
AimsCarotid artery disease is frequent and can result in chronic modest hypoperfusion of the brain. If no transient ischemic attack or stroke occur, it is classified asymptomatic. In the long-term, though, it can lead to cognitive impairment. Fostering cerebral remodeling after carotid artery occlusion might be a new concept of treatment. Paracrine Interleukin 6 (IL-6) can induce such remodeling processes at early stages. However, it has neurodegenerative long-term effects. With this exploratory study, we investigated the effect of paracrine IL-6 on cerebral remodeling in early stages after asymptomatic carotid artery occlusion to identify new treatment targets.Methods and ResultsTo mimic a human asymptomatic carotid artery disease, we used a mouse model of unilateral common carotid artery (CCA) occlusion. We developed a mouse model for inducible paracrine cerebral IL-6 expression (Cx30-Cre-ERT2;FLEX-IL6) and induced IL-6 2 days after CCA occlusion. We studied the effects of paracrine IL-6 after CCA occlusion on neuronal connectivity using diffusion tensor imaging and on local proteome regulations of the hypo-perfused striatum and contralateral motor cortex using mass spectrometry of laser capture micro-dissected tissues. Paracrine IL-6 induced cerebral remodeling leading to increased inter-hemispheric connectivity and changes in motor system connectivity. We identified changes in local protein abundance which might have adverse effects on functional outcome such as upregulation of Synuclein gamma (Sncg) or downregulation of Proline Dehydrogenase 1 (Prodh). However, we also identified changes in local protein abundance having potentially beneficial effects such as upregulation of Caprin1 or downregulation of GABA transporter 1 (Gat1).ConclusionsParacrine cerebral IL-6 at early stages induces changes in motor system connectivity and the proteome after asymptomatic CCA occlusion. Our results may help to distinguish unfavorable from beneficial IL-6 dependent protein regulations. Focusing on these targets might generate new treatments to improve long-term outcome in patients with carotid artery disease.